Guided Bone Regeneration with Occlusive Titanium Barrier: A Case Report and Clinical Considerations - Lucio Milillo; Massimo Petruzzi (Biomimetics, 2023)
The need to obtain adequate bone volumes for prosthetic rehabilitation supported by implants, using different techniques and materials, represents an urgent need in modern dentistry. We report a case regarding the management of implant-prosthetic rehabilitation of the first and second upper right molars, in which no less than 4 mm of crestal bone remained to insert two implants. Regeneration of the residual bone was previously performed using a customized titanium barrier and a filler of a blood clot with tricalcium beta phosphate. The bone gain (3 mm) was evaluated by comparing CBCT images, while the implant stability (mean 70) was assessed with the ISQ measurement. A regenerated bone sample was taken for histological analysis. Guided bone regeneration obtained with a titanium barrier and blood clot allowed for the insertion of stable implants in a mature bone without heterologous material.